Analyzing the Efficient Execution of In‐Store Logistics Processes in Grocery Retailing—The Case of Dairy Products. (23rd February 2013) - Reiner, Gerald; Teller, Christoph; Kotzab, Herbert
Abstract : In this article, we examine in‐store logistics processes for handling dairy products, from the incoming dock to the shelves of supermarkets and hypermarkets. The efficient execution of the in‐store logistics related to such fast‐moving, sensitive, and essential items is challenging and crucial for grocery retailers' sales, profits, and image. In our empirical study, we survey in‐store logistics processes in 202 grocery supermarkets and hypermarkets belonging to a major retail chain in central Europe. Using a data envelopment analysis (DEA) and simulation, we facilitate process benchmarking. In particular, we identify ways of improving in‐store logistics processes by showing the performance impacts of different managerial strategies and tactics. The DEA results indicate different efficiency levels for different store formats; the hybrid store format of the small hypermarket exhibits a comparatively worse performance in the analyzed execution of in‐store logistics processes. The process simulation analysis reveals that the strategic and tactical design of in‐store logistics processes (such as store locations/layouts, capacity management, reorder time, order period, and safety stock factors) lead to substantial service performance improvements (such as higher on‐shelf availability combined with reduced inventory obsolescence costs). The results also show marginal improvements in the performance figures when delivery delays and damage to products are reduced.